Case report: Treatment of non-medical tetrahydrocannabinol toxicosis with transmucosal cannabidiol-infused dissolving sheets in six dogs - Marsigliano, Kyra; Green, Katie; DiGangi, Brian A. (Frontiers in Veterinary Science, 2024)
Increased cases of canine tetrahydrocannabinol (THC) toxicosis have been reported in North America in recent years. Cases are often evaluated on an emergency basis and treatment has relied upon supportive care which can be costly and prohibitive for some pet owners. The purpose of this report is to describe the clinical findings and outcomes in dogs with non-medical, presumptive THC toxicosis treated by administration of a cannibidiol (CBD)-infused transmucosal dissolving sheet. Medical records of six cases of non-medical, presumptive THC toxicosis from a private primary care practice and a private after-hours emergency practice were reviewed and summarized. Five of six cases were treated exclusively with transmucosal CBD (0.4–2.6 mg/kg); one case also received injectable anti-emetic therapy. Lethargy and ataxia noticeably improved and all additional clinical signs resolved within 45 min of treatment in five of six cases. No further follow-up measures for THC toxicosis were required in any case; one case required additional follow-up for presumably unrelated gastrointestinal distress. This is the first report of treatment of canine THC toxicosis by administration of CBD. The use of transmucosal CBD-infused dissolving sheets resulted in expedient resolution of clinical signs in a minimally invasive manner that is accessible to both clients and veterinary practitioners.